PERBEDAAN KEAKTIFAN BELAJAR DAN HASIL BELAJAR KOGNITIF PLH PADA KONSEP ETIKA LINGKUNGAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN TIPE TEAMS GAME TOURNAMENT(TGT). - Popo Musthofa Kamil (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2016)
This study attempts to (1) knows the difference liveliness student learning state of the cooperative learning model type numbered heads together (NHT) with model cooperative learning type teams game tournament (TGT). (2) know the difference of the results learn cognitive students state of the learning model cooperative type numbered heads together (NHT) with model cooperative learning type teams game tournament (TGT). This research uses the method quasi eksperiment. Design research is post test group desaind. Based on the research done, (1) there is a difference liveliness student learning between use the model cooperative learning type numbered heads together (NHT) apply in the class X-2 and model cooperative learning type teams game tournament (TGT) apply in the class x-6 the concept ethics environment. It is based on the results of observation which showed that the average score class x-2 obtain the average 11,74 more better than class x-6 received an average of 22,98.cooperative learning model numbered heads together, teams game tournament, results cognitive study, liveliness learning